How to account for tax planning and its uncertainty in firm valuation? - Jonas Knaisch (Journal of Business Economics, 2023)
I compare two approaches from the recent literature on how to account for tax planning and its uncertainty in a valuation framework [the separate view of Drake et al. (J Account Audit Financ 34(1):151–176, 2019) vs. the composite view of Jacob and Schütt (Eur Account Rev 29(3):409–435, 2020)], emphasizing measurement issues of tax planning and firm heterogeneity. Replication analyses and extensive robustness tests suggest that only considering tax planning and it's uncertainty jointly and connecting them to firm value via income leads to consistent results, implying that higher uncertainty-adjusted tax planning amplifies the positive association between pre-tax income and firm value. However, the economic magnitude of this association depends on the measurement approach, ranging between 0.8 and 12.91%. Conversely, the separate view produces inconsistent results in all tests. These conclusions are not affected by incorporating recent losses (Dyreng et al. in Tax avoidance or recent losses? Working Paper, 2021) when an appropriate tax planning measure is chosen. While the results become insignificant when effective tax rates are used, applying the measure of Henry and Sansing (Rev Account Stud 23:1042–1070, 2018) mitigates this problem. Moreover, the positive value implication of uncertainty-adjusted tax planning is particularly pronounced for firms with low leverage whose debt tax shield and debt overhang are relatively small. The logic of jointly measuring tax planning and its uncertainty seems to be extendable to a variety of measures and to provide a more suitable measure than traditional isolated effective tax rates in a valuation framework.
Keywords: G32; H25; H26; M21; M41; 650; Tax planning; Tax uncertainty; Firm value; Tax planning score